Ebola Virus Infections in Nonhuman Primates Are Temporally Influenced by Glycoprotein Poly-U Editing Site Populations in the Exposure Material - John C. Trefry; Suzanne E. Wollen; Farooq Nasar; Joshua D. Shamblin; Steven J. Kern; Jeremy J. Bearss; Michelle A. Jefferson; Taylor B. Chance; Jeffery R. Kugelman; Jason T. Ladner; Anna N. Honko; Dean J. Kobs; et al. (Viruses, 2015)
Recent experimentation with the variants of the Ebola virus that differ in the glycoprotein’s poly-uridine site, which dictates the form of glycoprotein produced through a transcriptional stutter, has resulted in questions regarding the pathogenicity and lethality of the stocks used to develop products currently undergoing human clinical trials to combat the disease. In order to address these concerns and prevent the delay of these critical research programs, we designed an experiment that permitted us to intramuscularly challenge statistically significant numbers of naïve and vaccinated cynomolgus macaques with either a 7U or 8U variant of the Ebola virus, Kikwit isolate. In naïve animals, no difference in survivorship was observed; however, there was a significant delay in the disease course between the two groups. Significant differences were also observed in time-of-fever, serum chemistry, and hematology. In vaccinated animals, there was no statistical difference in survivorship between either challenge groups, with two succumbing in the 7U group compared to 1 in the 8U challenge group. In summary, survivorship was not affected, but the Ebola virus disease course in nonhuman primates is temporally influenced by glycoprotein poly-U editing site populations.